2017
DOI: 10.1016/j.soard.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Fat-free mass is not lower 24 months postbariatric surgery than nonoperated matched controls

Abstract: Objective Concerns about an excessive loss of fat-free mass (FFM) after bariatric surgery prompted this comparison of operated versus matched nonoperated controls regarding FFM. Setting University Hospital and University Research Unit in an urban medical center. Methods Body composition with bioelectric impedance (Tanita 310, Tanita Corp, Arlington Heights, IL) was measured approximately 2 years after bariatric surgery in weight stable patients and nonoperated weight stable controls matched for body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Early observations by Forbes ( 24 ) point to a close linkage between body weight and FFM, such that some FFM loss is expected during body weight loss. Indeed, results from numerous studies have shown FFM losses of similar magnitude or greater than this study during rapid weight loss in the first 1–2 years after RYGB ( 7 , 25 , 26 , 27 , 28 , 29 , 30 ), SLEEVE ( 7 , 25 , 28 , 29 ), and BAND ( 7 , 26 , 27 , 31 , 32 , 33 ) procedures. The rate and amount of FFM lost during these initial post-operative years may vary by surgical procedure, extent of weight loss, and possibly assessment method.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Early observations by Forbes ( 24 ) point to a close linkage between body weight and FFM, such that some FFM loss is expected during body weight loss. Indeed, results from numerous studies have shown FFM losses of similar magnitude or greater than this study during rapid weight loss in the first 1–2 years after RYGB ( 7 , 25 , 26 , 27 , 28 , 29 , 30 ), SLEEVE ( 7 , 25 , 28 , 29 ), and BAND ( 7 , 26 , 27 , 31 , 32 , 33 ) procedures. The rate and amount of FFM lost during these initial post-operative years may vary by surgical procedure, extent of weight loss, and possibly assessment method.…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies assessed FFM in bariatric surgery patients soon after weight loss compared with weight‐ and age‐matched controls and found the same or even greater FFM than expected within their BMI category . While these findings appear promising for bariatric surgery patients, it is important to note that most of the studies of FFM after surgically induced weight loss do not extend beyond the initial weight‐loss period (1‐2 years) .…”
Section: Introductionmentioning
confidence: 91%
“…This is supported by studies demonstrating higher FFM percentages after both RYGB and SG compared with unoperated controls, inconsistent with major FFM depletion after surgery. 50 Instead, the loss of FFM seems comparable to what is expected due to the weight loss itself. 51 The cross-sectional design of our study has the advantage that we were able to examine patients in the weightstable phase and to obtain matching for both pre-and postoperative BMI to minimize the confounding effect of differing postoperative weight losses.…”
Section: Discussionmentioning
confidence: 90%